SDF-1/CXCL12 and CXCR4 gene variants, and elevated serum SDF-1 levels are associated with preeclampsia - Savas Karakus; Binnur Bagci; Gokhan Bagci; Enver Sancakdar; Caglar Yildiz; Ozlem Akkar; Ali Cetin (Taylor & Francis Group, 2017)
Objective: We aimed to compare the frequencies of stromal cell-derived factor-1 (SDF-1) 3'A and CXCR4 single-nucleotide polymorphisms (SNPs) and serum SDF-1 levels in patients with preeclampsia (PE). Methods: In total, 89 women with PE and 89 control women were included in the study. Genotyping was done by polymerase chain reaction-restriction fragment length polymorphism method. Enzyme-linked immunosorbent assay method was used to measure serum SDF-1 level. Results: For SDF-1 3'A SNP, the frequency of GA genotype, total number of GA and AA genotypes, and the A allele frequency was higher in PE patients than controls (p = 0.04, 0.023, and 0.029, respectively). For CXCR4 SNP, the frequency of CT genotype, total number of CT and TT genotypes, and the T allele frequency were higher in PE patients than controls (p = 0.04, 0.006, and 0.005, respectively). SDF-1 serum level was detected higher in preeclamptic women compared with controls (p = 0.001). In PE patients, there was no significant association between serum SDF-1 levels and genotypes of SDF-1 3'A SNP. SDF-1 level was significantly higher in patients bearing CXCR4 CT genotype than CC genotype (p = 0.001). Furthermore, SDF-1 levels in patients bearing CT+TT genotype were found higher than that of patients with CC genotypes (p = 0.001). Conclusion: Results of our study suggest that SDF-1 3'A and CXCR4 polymorphisms and elevated serum SDF-1 levels may have a role in the development of PE.